2010
DOI: 10.1038/nrrheum.2010.176
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to systemic lupus erythematosus in the genomic era

Abstract: Our understanding of the genetic basis of systemic lupus erythematosus (SLE) has been rapidly advanced using large-scale, case–control, candidate gene studies as well as genome-wide association studies during the past 3 years. These techniques have identified more than 30 robust genetic associations with SLE including genetic variants of HLA and Fcγ receptor genes, IRF5, STAT4, PTPN22, TNFAIP3, BLK, BANK1, TNFSF4 and ITGAM. Most SLE-associated gene products participate in key pathogenic pathways, including Tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
240
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(252 citation statements)
references
References 115 publications
4
240
0
5
Order By: Relevance
“…at multiple genetic loci are believed to increase the risk of SLE in a hierarchical interactive manner [Moser et al 2009;Nath et al 2004]. Although extensive studies have associated many common genetic variants with SLE [Deng and Tsao, 2010;Flesher et al 2010], the cumulative effect size of the loci identified so far accounts for only 15-20% of the heritability of SLE [Manolio et al 2009]. The variations potentially underlying the remaining 75-80% of the heritability appear to be missing.…”
Section: Biomarkers Originated From Better Understanding Of Sle Pathomentioning
confidence: 99%
“…at multiple genetic loci are believed to increase the risk of SLE in a hierarchical interactive manner [Moser et al 2009;Nath et al 2004]. Although extensive studies have associated many common genetic variants with SLE [Deng and Tsao, 2010;Flesher et al 2010], the cumulative effect size of the loci identified so far accounts for only 15-20% of the heritability of SLE [Manolio et al 2009]. The variations potentially underlying the remaining 75-80% of the heritability appear to be missing.…”
Section: Biomarkers Originated From Better Understanding Of Sle Pathomentioning
confidence: 99%
“…Candidate gene studies and, more recently, genome-wide association studies (GWAS), have begun to elucidate the complex genetic profile of systemic lupus erythematosus (SLE) with identification of ∼30 risk loci (1)(2)(3). However, for almost all these identified loci, the causal polymorphism that leads to lupus susceptibility has not been discovered.…”
mentioning
confidence: 99%
“…Recent genome-wide association studies (GWAS) have identified a number of single-nucleotide polymor-phisms (SNPs) associated with the risk of SLE, in genes such as HLA, IRF5, STAT4, TNFAIP3, PTPN22, BLK, BANK1, TNFSF4, ITGAM, KIAA1542, and PXK, in various ethnic groups (2). In addition to SNPs, DNA copy number variations (CNVs) can influence the interindividual differences in the risk of disease via several mechanisms that affect gene expression, such as gene disruption and rearrangements (3)(4)(5).…”
mentioning
confidence: 99%